the concept of civil society in the perspective of Islamic education - andini, wulan (Maliki Interdisciplinary Journal, 2025)
This paper examines the concept of madani society (civil society) from the perspective of Islamic education as an effort to build a civilized, democratic social order based on Islamic values. A madani society is understood as a community that upholds morality, social justice, tolerance, and pluralism, while emphasizing the rule of law and respect for human rights. In Islamic tradition, this concept was historically implemented in the society of Madinah established by the Prophet Muhammad (peace be upon him) through the Constitution of Madinah, which promoted peaceful coexistence among religious and ethnic groups. This study employs a qualitative descriptive approach through literature review and historical analysis. Islamic education is positioned as a vital tool in shaping a madani society due to its central role in developing individuals who are religious, intelligent, and have strong integrity. By emphasizing the four pillars of education—learning to know, learning to do, learning to be, and learning to live together—Islamic education is expected to produce generations capable of addressing global challenges while preserving Islamic and national values. Reforming Islamic education is an urgent need, particularly in terms of integrating religious and secular knowledge, strengthening curricula relevant to contemporary developments, and improving the quality of educators and educational management